2021
DOI: 10.1109/mts.2021.3056294
|View full text |Cite
|
Sign up to set email alerts
|

AI Ethics for Sustainable Development Goals

Abstract: 1 Algorithms are here to stay. They are transforming the way we live and work and increasingly replace cognitively human ways of making decisions. The so called "algorithmocracy" or the ecosystem that we all now inhabit, where algorithms govern many aspects of our behavior, has the potential to bias and be deployed at large scales. Because the automation of decisions by algorithms promise efficiency and resource maximization, AI technologies can be used to meet the 17 Sustainable Development Goals and its 169 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The article contributes to the development of the concept of environmental economics and management by substantiating the new role that AI should play in its framework. Unlike Astobiza et al (2021), Bolton et al (2021), Choi et al (2021), Minkkinen et al (2022), Osipov et al (2022), Popkova et al (2020), Saetra (2021), Visvizi (2022), and Wilson and van der Velden (2022), it has been proved that the existing interpretation of sustainable AI does not allow to unlock the potential of AI to fight new global challenges and therefore needs to be revised. Distinctive features of the proposed new authors' interpretation are: → The transition from the practice of flexible redirection of AI from one industry to another (for example, in healthcare, in the context of the COVID-19 pandemic) to a fixed, stable, and long-term application of sustainable AI in environmental economics and management; → Sustainable AI should be given a new role related to preventive environmental crisis management (as opposed to dealing with current threats, which is a characteristic of the existing interpretation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article contributes to the development of the concept of environmental economics and management by substantiating the new role that AI should play in its framework. Unlike Astobiza et al (2021), Bolton et al (2021), Choi et al (2021), Minkkinen et al (2022), Osipov et al (2022), Popkova et al (2020), Saetra (2021), Visvizi (2022), and Wilson and van der Velden (2022), it has been proved that the existing interpretation of sustainable AI does not allow to unlock the potential of AI to fight new global challenges and therefore needs to be revised. Distinctive features of the proposed new authors' interpretation are: → The transition from the practice of flexible redirection of AI from one industry to another (for example, in healthcare, in the context of the COVID-19 pandemic) to a fixed, stable, and long-term application of sustainable AI in environmental economics and management; → Sustainable AI should be given a new role related to preventive environmental crisis management (as opposed to dealing with current threats, which is a characteristic of the existing interpretation).…”
Section: Discussionmentioning
confidence: 99%
“…The existing interpretation of sustainable AI defines it as smart technology for maintaining stable and balanced development of economic systems (Popkova et al, 2020;Saetra, 2021;Minkkinen et al, 2022;Osipov et al, 2022). Threats to healthcare have become more acute in the context of a pandemic; therefore, based on the existing interpretation, medicine has become the main area of application of sustainable AI (Astobiza et al, 2021;Bolton et al, 2021;Choi et al, 2021;Visvizi, 2022;Wilson and van der Velden, 2022). The advantage of the current interpretation is that it allows flexibly rebuilding a stable AI, applying it in the most demanded areas (Popkova et al, 2022a;Popkova et al, 2022b;Popkova and Sergi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Even though power companies collect and retain data, it is difficult to digitize it with modern management software. Data loss, improper configuration, device failure, and illegal access are all risks that are linked . The most significant impediment to the energy sector’s modernization is outdated infrastructure.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Astobiza, et al [38] suggested that we live in a golden age, whereby global issues such as climate change exist, and responses to such issues must be organized at the global scale. Astobiza, et al [38] believe that, as AI progresses, many academics are investigating the prospect of using it to solve societal problems, which is a concept known as AI for social good. AI for social good refers to the use of AI-powered technologies and capabilities to promote public welfare.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%